﻿Commelina danxiaensis (Commelinaceae), a new species from Guangdong, China - Long-Yuan Wang; Wan-Yi Zhao; Zai-Xiong Chen; Wei-Cheng Huang; Ming-Yan Ding; Jin-Chu Luo; Wen-Bo Liao; Wei Guo; Qiang Fan (PhytoKeys, 2023)
Commelina danxiaensis (Commelinaceae), a remarkable new species from Mount Danxia, Guangdong Province, China, is described and illustrated. This species is similar to C. communis in inflorescences and flowers but readily distinguishable in its nearly erect stems, larger flowers, and different petal colouration.